Building the Internet of Things, by Maciej Kranz (IITM Journal of Business Studies, 2024)
Through the book "Building the Internet of Things", Author MaciejKranz, Vice President of the Strategic Innovations Group at Cisco aimsto bring the knowledge of rhe "Intcrner ofThings" (loT) in rhe mindsof the Present Business Managers and the potential Managers of theFumre. Right from the first Chapter of the Book, Kranz tells us whyIoT is essemial in roday's world, and how it is capable of shaping thefuture of Business Organizations.
Keywords: Business Organizations; Networks